Budget Processes: Theory and Experimental Evidence - Karl-Martin Ehrhart; Roy Gardner; Jürgen von Hagen; Claudia Keser (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
This paper studies budget processes, both theoretically and experimentally. We compare the outcomes of bottom-up and top-down budget processes. It is often presumed that a top-down budget process leads to a smaller overall budget than a bottom-up budget process. Ferejohn and Krehbiel (1987) showed theoretically that this need not be the case. We test experimentally the theoretical predictions of their work. The evidence from these experiments lends strong support to their theory, both at the aggregate and the individual subject level.
urn:nbn:de:bvb:19-epub-13405-9
Keywords: H61; C91; C92; 330; Budget processes; voting equilibrium; experimental economics